2000
DOI: 10.1161/01.hyp.36.5.760
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Contribution of Cardiac and Arterial Remodeling to Hypertension

Abstract: Abstract-The study aim was to quantify the individual and combined contributions of both the arterial system and the heart to systolic blood pressure in hypertension. We assessed the parameters of a heart-arterial model for normotensive control subjects and hypertensive patients with left ventricular adaptation patterns classified as normal, concentric remodeling, concentric hypertrophy, or eccentric hypertrophy. The present simulations show that vascular stiffening alone increases the pulse pressure without i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 38 publications
4
60
0
Order By: Relevance
“…The four-element Windkessel has been used by Segers [51,[53][54][55] and Burattini [5]. In practice it turns out that the inertance is very difficult to estimate which is an argument to prefer the three-element Windkessel.…”
Section: The Four-element Windkesselmentioning
confidence: 99%
See 1 more Smart Citation
“…The four-element Windkessel has been used by Segers [51,[53][54][55] and Burattini [5]. In practice it turns out that the inertance is very difficult to estimate which is an argument to prefer the three-element Windkessel.…”
Section: The Four-element Windkesselmentioning
confidence: 99%
“…Several studies have been reported on ventriculo-arterial coupling. In these studies Windkessel models of the arterial system have been used [10,52,54,55]. The Windkessel as load is preferred in this type of analysis since more extensive models are awkward to work with.…”
Section: Use and Clinical Relevance Of The Windkesselmentioning
confidence: 99%
“…[15] Another choice for the value of total arterial compliance would lead to different R-R L,ao solutions in the 3 subgroups. To assess the impact of this assumption, extra simulations are done with all parameters kept constant, except that C is increased and decreased by 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these data must be estimated in an indirect way. Fixed values are assumed for L (0.005 mm Hg·s 2 /mL) and Z 0 (0.033 mm Hg·s/mL), [15] 2 parameters that have been shown to have limited impact on pressure and flow. [14] It is further assumed that total arterial compliance does not differ between the subgroups, being 1.15 mL/mm Hg, a value that we have found in another study for age-matched hypertensive patients.…”
Section: Arterial Parameters and Aortic Valve Leakagementioning
confidence: 99%
See 1 more Smart Citation